Penerapan Konsep Manajemen Pendidikan untuk Meningkatkan Kompetensi Guru - Ahyani, Edi (Indo-MathEdu Intellectuals Journal, 2023)
This article discusses the application of education management concepts to improve teacher competence as the main driver in the learning process. This study aims to discuss the most effective education management strategies in improving teacher competence to implement effective learning programs. The analysis technique used is a literature study involving the identification, selection, and evaluation of library sources relevant to the research topic. This process includes information synthesis, data organization, and codification to uncover key patterns and findings from the literature Analysis results are included in the report to support or stimulate research questions. The results of this study show that the application of effective education management concepts to improve teacher competence includes the development of managerial skills that include planning, implementing, supervising and evaluating in the learning process. It is hoped that this article can provide input for decision makers and stakeholders in the field of education to improve the quality and effectiveness of learning in schools